Current Concepts of Hyperinflammation in Chronic Granulomatous Disease - Nikolaus Rieber; Andreas Hector; Taco Kuijpers; Dirk Roos; Dominik Hartl (Clinical and Developmental Immunology)
Chronic granulomatous disease (CGD) is the most common inherited disorder of phagocytic functions, caused by genetic defects in the leukocyte nicotinamide dinucleotide phosphate (NADPH) oxidase. Consequently, CGD phagocytes are impaired in destroying phagocytosed microorganisms, rendering the patients susceptible to bacterial and fungal infections. Besides this immunodeficiency, CGD patients suffer from various autoinflammatory symptoms, such as granuloma formation in the skin or urinary tract and Crohn-like colitis. Owing to improved antimicrobial treatment strategies, the majority of CGD patients reaches adulthood, yet the autoinflammatory manifestations become more prominent by lack of causative treatment options. The underlying pathomechanisms driving hyperinflammatory reactions in CGD are poorly understood, but recent studies implicate reduced neutrophil apoptosis and efferocytosis, dysbalanced innate immune receptors, altered T-cell surface redox levels, induction of Th17 cells, the enzyme indolamine-2,3-dioxygenase (IDO), impaired Nrf2 activity, and inflammasome activation. Here we discuss immunological mechanisms of hyperinflammation and their potential therapeutic implications in CGD.